Colegios mayores of Peru: past and present - Robles Ortiz , Elmer (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: To compare the characteristics of the colegios mayores from the period of Hispanic domination and the nineteenth century republic with their new version of the 21st century, in the context of the history and social processes of contemporary Peru in search of its integral development. Originality/support: This study makes a significant contribution to the clarification of the historical process of the colegios mayores in Peru. For this purpose, the information was systematized, including relevant data such as their origin, importance and the roles played by their most outstanding graduates. Method: The research material has a dual approach. It comprises, on the one hand, ideas and achievements of the past, and on the other hand, it refers to current events. In both cases, a diachronic analysis is carried out. Both the research and the interpretation of the data are qualitative in nature. Strategies/Data collection: The search for information was carried out in primary and secondary sources, as well as on websites. Some of the sources date back to the time when the colegios mayores were founded during the colonial period. All data were subjected to analysis and interpretation. Conclusions: We can distinguish three moments of historical relevance. First, colegios mayores of the 16th to 18th centuries (San Pablo, San Martin, and San Felipe and San Marcos), then those that emerged in the 18th century and moved into the 19th century (Convictorio de San Carlos and Colegio de San Fernando), and the high performance ones (COAR -for the spelling in Spanish-) of the 21st century, an advantageous modality with respect to common secondary education. But there are other cases, of high schools, which at one point offered university level subjects. Among their students, notable figures in law, education, literature, economics, politics and science have emerged. The Peruvian educational system, accused of various shortcomings, has in the COARs the potential to project quality-oriented alternatives.